2016
DOI: 10.1007/s10842-016-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Decisions in Dual-Channel Supply Chain Including Monopolistic Manufacturer and Duopolistic Retailers: A Game-Theoretic Approach

Abstract: Emergence of the Internet as a new distribution channel has led to increasing attention by researchers to dual-channel supply chain in recent years. In this paper, pricing and ordering decisions are investigated on a dual-channel supply chain which consists of monopolistic manufacturer and duopolistic retailers. The market is assumed to be controlled by the manufacturer. Thus, the manufacturer becomes leader and the two retailers act as followers. Due to establishing this new structure, different game-theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Furthermore, this practice could enhance a company's corporate image. Jafari, Hejazi, and Rasti-Barzok [162] and Ngai et al [163] explored the interaction between retailers and consumers, offering supply chain solutions, and they concluded that focusing on this boosts the brand image for retailers. Schaltegger and Wagner [7] and Kopnina and Blewitt [34] found that promoting and applying sustainable practices in the company gives multiple benefits, such as improving a company's image and increasing profitability.…”
Section: Supply Chain and Imagementioning
confidence: 99%
“…Furthermore, this practice could enhance a company's corporate image. Jafari, Hejazi, and Rasti-Barzok [162] and Ngai et al [163] explored the interaction between retailers and consumers, offering supply chain solutions, and they concluded that focusing on this boosts the brand image for retailers. Schaltegger and Wagner [7] and Kopnina and Blewitt [34] found that promoting and applying sustainable practices in the company gives multiple benefits, such as improving a company's image and increasing profitability.…”
Section: Supply Chain and Imagementioning
confidence: 99%
“…We use o, s, and os to denote the three scenarios, respectively. (4) e manufacturer, as the leader, plays the Stackelberg game with the retailer [17,26,49,50]. e reason is that the manufacturer may have more bargaining power than the retailer because he has its own channel.…”
Section: The Modelmentioning
confidence: 99%
“…Furthermore, this practice could enhance a company´s corporate image. Jafari, Hejazi, and Rasti-Barzok [139] and Ngai, Law, Lo, Poon, and Peng [140] have explored the interaction between retailers and consumers, offering supply chain solutions, and they conclude that focusing on this boosts the brand image for retailers. Schaltegger and Wagner [7] and Kopnina and Blewitt [34] found that promoting and applying sustainable practices in the company gives multiple benefits, such as improving a company's image and increasing profitability.…”
Section: Supply Chain and Imagementioning
confidence: 99%